2020
DOI: 10.1590/0100-6991e-20202703
|View full text |Cite
|
Sign up to set email alerts
|

Surgical results of remnant gastric cancer treatment

Abstract: Background: remnant gastric cancer (RGC) develops five years or later after previous resection for benign or malignant lesion. The treatment is performed through completion total gastrectomy (CTG) with radical lymphadenectomy. Some reports consider this procedure may be associated with higher rates of morbidity and mortality. Objective: to evaluate surgical results and survival after CTG in patients with RGC. Methods: 54 patients who underwent CTG between 2009 and 2019 were included in the study. As a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…In any case, the endoscopist should be more careful when performing ESD in the remnant stomach or gastric tube, to avoid perforations because of the previously mentioned anatomic features. On the other hand, the complication rate was higher in the present study than in surgery for primary EGC as reported, and the reason may be the formation of more extensive adhesions caused by the lymphadenectomy in the previous surgery [34].…”
Section: Discussioncontrasting
confidence: 58%
“…In any case, the endoscopist should be more careful when performing ESD in the remnant stomach or gastric tube, to avoid perforations because of the previously mentioned anatomic features. On the other hand, the complication rate was higher in the present study than in surgery for primary EGC as reported, and the reason may be the formation of more extensive adhesions caused by the lymphadenectomy in the previous surgery [34].…”
Section: Discussioncontrasting
confidence: 58%
“…The prognosis of GRC remains controversial. Some studies have reported that GRC shows similar prognosis to primary gastric cancer[ 20 - 22 ], whereas others have argued that the prognosis for GRC is worse[ 3 , 9 , 23 ]. In our study, we only enrolled patients with locally advanced GRC and 73.9% (67/74) of the patients were stage II or stage III.…”
Section: Discussionmentioning
confidence: 99%
“…It is technically difficult due to previous surgery, but possible if diagnosed early in a well-performing patient. Short-term outcomes such as hospital stay, 30-day mortality, and long-term outcomes such as disease-free survival and overall survival were similar between primary gastric cancer and GSC patient groups when curative resection of GSC is possible [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The interval between the first and second surgeries in the patient population varied significantly depending on the underlying disorder (p <0.001). Patients with a history of benign disease developed GSC median 30 years after previous surgery (mean 24.42 ± 9.44 years). On the other hand, all patients with a history of gastric cancer developed GSC by 5-10 years of primary surgery (mean 6.0 ± 0.96).…”
Section: Demographicsmentioning
confidence: 99%